(untitled) (Pilquen Magazine. Psychopedagogy Section, 2023)
Matices de la excepcionalidad, aprender en pandemia is a book published by María Angélica in 2022. The author is an Argentinian psychopedagogue who has written other works related to psychopedagogical practice, especially clinical practice. Undoubtedly, her books are a source of information for colleagues and form part of the bibliography of the curricula of various psychopedagogy courses in the country.